Development and Effectiveness of Golwan Interactive Multimedia as Teaching Material for Animal Classification Based on Food - Agesti, Avrilliani; Aeni, Ani Nur; Sujana, Atep (Jurnal Pendidikan MIPA, 2023)
Abstract: Human behavior is increasingly changing along with the massive development of technology to the point that it can change how we communicate. Unfortunately, many teachers are still not proficient in using technology, making learning feel less concrete and exciting for students. The aims of this research are to develop interactive media based on Ispring, to describe the feasibility of the Golwan learning application, to describe the practicality of interactive media based on Ispring and the use of the additional website 2 apk android builder application as the final result of this learning application. This research method uses MDLC (multimedia Development Life Cycle) with six stages: concept, design, material collection, creation, testing, and distribution, by using data collection instruments in the form of questionnaires, unstructured interviews, and documentation. And the test subjects were for fourth-grade students at SDN 2 Karangsuwung. The research results state that Android-based interactive multimedia applications are suitable for use. By fulfilling the media expert test percentage of 83%. The percentage of assessment by material experts was obtained at 90%. The percentage assessment of prospective use is 91%. Response from potential users with limited testing got a percentage of 90%. What is classified as interactive multimedia (Golwan) is declared appropriate or very good as a learning media tool. Keywords: interactive multimedia, classifying animals based on their food, ispring, website 2 apk android builder Abstrak: Tingkah laku manusia kian berubah seiring masifnya perkembangan teknologi sampai bisa mengubah cara berkomunikasi dan cara mengajar di kelas. Sayangnya masih banyak guru yang belum mahir dalam penggunaan teknologi. Menjadikan pembelajaran dirasa kurang konkrit dan menarik bagi peserta didik. Tujuan penelitian ini adalah mengembangkan media interaktif berasis Ispring, mendeskripsikan kelayakan aplikasi pembelajaran Golwan mendeskripsikan kepraktisan media interaktif berbasis Ispring serta penggunaan aplikasi tambahan website 2 apk android builder sebagai hasil akhir aplikasi pembelajaran ini. Metode penelitian ini menggunakan MDLC (multimedia Development Life Cycle) dengan enam tahapan : konsep, desain, pengumpulan materi, pembuatan, pengujian, pendistribusian. Dengan menggunakan instrumen pengumpulan data berupa angket, wawancara tidak terstruktur, dokumentasi. Dan subjek uji coba kepada siswa kela IV di SDN 2 Karangsuwung. Hasil penelitian menyatakan bahwa aplikasi multimedia interaktif berbasis android layak untuk dipergunakan. Dengan memenuhi presentase uji ahli media sebesar 83%. Penilaian presentase uji ahli materi sebesar 90%. Penilaian presentase dari calon penggunaan sebesar 91%. Serta respon dari calon pengguna yang dilakukan dengan uji terbatas mendapatkan presentase 90%. Yang diklasifikasikan bahwa multimedia interaktif (Golwan) dinyatakan Layak atau sangat baik sebagai sarana media pembelajaran.  Kata kunci: Multimedia interaktif, pengolongan hewan berdasarkan makananya, Ispring, website 2 apk android builder DOI: http://dx.doi.org/10.23960/jpmipa/v24i4.pp769-783